2005
DOI: 10.1002/ijc.21400
|View full text |Cite
|
Sign up to set email alerts
|

Wnt pathway is involved in pleomorphic adenomas induced by overexpression of PLAG1 in transgenic mice

Abstract: Pleomorphic adenoma gene 1 (PLAG1) was found frequently rearranged and activated in human salivary gland pleomorphic adenomas. It encodes a developmentally regulated transcription factor. Ectopic overexpression of PLAG1 has been proposed to play a crucial role in tumorigenesis of salivary gland pleomorphic adenomas. It was reported that PLAG1 can activate the transcription of insulin-like growth factor 2 (IGF2), functioning as a protooncogene. In this report, we show that the salivary gland tumors developed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
0
38
1
Order By: Relevance
“…To explore the role of PLAG1 in neoplastic transformation in vivo in the context of a complex organism, transgenic mouse strains were developed (2,44). The most versatile strains are conditional transgenics in which activation of overexpression of the PLAG1 transgene as well as the tissue distribution of such overexpression can be manipulated (e.g., by Cre-mediated activation and targeted expression, respectively) (Fig.…”
Section: Oncogenic Capacity Of Plag1 In Vivomentioning
confidence: 99%
“…To explore the role of PLAG1 in neoplastic transformation in vivo in the context of a complex organism, transgenic mouse strains were developed (2,44). The most versatile strains are conditional transgenics in which activation of overexpression of the PLAG1 transgene as well as the tissue distribution of such overexpression can be manipulated (e.g., by Cre-mediated activation and targeted expression, respectively) (Fig.…”
Section: Oncogenic Capacity Of Plag1 In Vivomentioning
confidence: 99%
“…Additionally, a recent report has shown that Wnt signaling pathway may be involved in pleomorphic adenomas induced by overexpression of Plag1 in transgenic mice, since these animals exhibited upregulation of b-catenin and c-myc, two major components of the Wnt pathway (Zhao et al, 2006).…”
Section: Role Of Growth Factor Signaling Pathwaymentioning
confidence: 99%
“…Also, recent reports have established a direct in vivo tumorigenic capacity of PLAG1 overexpression in pleomorphic salivary gland tumorigenesis in transgenic mice (Declercq et al, 2005;Zhao et al, 2006). It is believed that Wnt signaling pathway is involved in pleomorphic adenomas induced by overexpression of Plag1 in these transgenic mice, since they showed upregulation of b-catenin and c-myc, two components of the Wnt pathway (Zhao et al, 2006). As was noted above, PLAGL1/LOT1/ZAC1 inhibits proliferation of tumor cells by inducing cell-cycle arrest and apoptosis (Abdollahi et al, 1997a(Abdollahi et al, ,b, 1999Spengler et al, 1997).…”
Section: Gene Expression In Tumors and Cancer Cellsmentioning
confidence: 99%
“…The oncogenic capacity of PLAG1 has been demonstrated in vitro, i.e. in cell lines that were retrovirally transduced with PLAG1 (22), and recently, in vivo in mouse models (23,24). Whereas Zhao and co-workers generated classical, non-conditional transgenic mouse strains (24), we developed two independent PLAG1 transgenic mouse strains, PTMS1 and PTMS2, in which activation of overexpression of the transgene as well as the tissue distribution of such overexpression can be manipulated, by Cre-mediated activation and targeted expression, respectively (23).…”
Section: Introductionmentioning
confidence: 99%